THE INFLUENCE OF VISUAL MERCHANDISING AND BRAND EQUITY TOWARDS CONSUMER BUYING BEHAVIOR IN PEDRO STORE MANADO - Onesimus Simanungkalit, Onesimus; Worang, Frederik G.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Fashion retail has an important role in the business development process in every country. Every company maintains and develops their products from all aspects. The application of visual merchandising and brand equity is an important aspect in the sustainability of a fashion retailer and introducing their brand to customers. This study aims to analyze the influence of Visual Merchandising (X1) and Brand Equity (X2) towards Consumer Buying Behavior (Y) in Pedro Store Manado. The researcher conducted this research through quantitative methods. The multiple linear regression analysis method is used to analyze the effect of the independent variable on the dependent variable. This technique using purposive sampling and conducts with 100 respondents and processed using SPSS program. The result proved that visual merchandising and brand equity have a significant and positive influence towards consumer buying behavior in Pedro Store Manado partially and simultaneously.Â Keywords: visual merchandising, brand equity, consumer buying behavior